2007
DOI: 10.1007/s11745-007-3048-2
|View full text |Cite
|
Sign up to set email alerts
|

Spin‐Probe Investigations of Head Group Behavior in Aqueous Dispersions of a Nonionic Amphiphilic Compound

Abstract: Head group behavior of nonionic amphiphilic compound, (poly(oxyethylene) hydrogenated castor oil, HCO), in aqueous dispersions were investigated by EPR (electron paramagnetic resonance) in conjunction with a modern slow-tumbling simulation. The aliphatic spin probes, 5-doxylstearic acid (5-DSA) and 3beta-doxyl-5alpha-cholestane (CHL), were used to obtain fluidity of the surface region of the membrane. The order parameter (S (0)) using the simulation for 5-DSA and CHL in the region were approximately 0.4 and 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Hyperfine coupling constants A xx , A yy of 2.3 G and A zz of 27 G and the values of the gyromagnetic tensor g x 2.008, g y 2.006, and g z 2.002 were determined by simulating the experimental spectrum with Bruker SIMFONIA in a third‐order perturbation theory approach (with an error of 10%). The values of the EPR parameters are similar to that described in the literature for lipid bilayers and indicate that the nitroxide spin probe is immobilized in the vesicles membrane on the timescale relevant for CW‐EPR. 5‐DSA encapsulated in PEG loaded vesicles produced a more complex signal that consisted of a superposition of an anisotropic EPR pattern associated with the entrapment in the membrane siloxane layer (see above), and an isotropic pattern similar to that observed in both 0.1 m NaOH and 60 mg mL −1 PEG solution.…”
Section: Resultssupporting
confidence: 81%
“…Hyperfine coupling constants A xx , A yy of 2.3 G and A zz of 27 G and the values of the gyromagnetic tensor g x 2.008, g y 2.006, and g z 2.002 were determined by simulating the experimental spectrum with Bruker SIMFONIA in a third‐order perturbation theory approach (with an error of 10%). The values of the EPR parameters are similar to that described in the literature for lipid bilayers and indicate that the nitroxide spin probe is immobilized in the vesicles membrane on the timescale relevant for CW‐EPR. 5‐DSA encapsulated in PEG loaded vesicles produced a more complex signal that consisted of a superposition of an anisotropic EPR pattern associated with the entrapment in the membrane siloxane layer (see above), and an isotropic pattern similar to that observed in both 0.1 m NaOH and 60 mg mL −1 PEG solution.…”
Section: Resultssupporting
confidence: 81%
“…In contrast, OmpF-S-S-NO gave a broad anisotropic EPR spectrum with no isotropic component, and is similar to that reported for 5-DSA in lipid bilayers or cholesterol aqueous solutions 48 . This EPR spectrum indicates hindered rotation of the nitroxide probe 49 after binding to the OmpF mutant (OmpF-S-S-NO), and demonstrates successful binding of the bis-(2,2,5,5-tetramethyl-3-imidazoline-1-oxyl-4-yl) disulphide to the modified OmpF mutant (Fig. 2a ).…”
Section: Resultsmentioning
confidence: 83%
“…The results can be due to different molecular motions of CHL having aromatic rings and its location in the membrane. It was also suggested that EPR and EPR simulation for the cholesterol derived probe remain preferentially in the liquid ordered region of the detergent-resistant membrane [18]. The experimental errors are presented in Fig.…”
Section: T 1e Of the Head Group Regionmentioning
confidence: 93%
“…7. The T 1e values obtained are listed in Table 1 together with the various values obtained by EPR slow-tumbling simulation [12,13,18]. The T 1e for CHL is slightly longer than one for 5-DSA.…”
Section: T 1e Of the Head Group Regionmentioning
confidence: 94%
See 1 more Smart Citation